Analisa Kekerasan Baja Carbon Steel 1045 Akibat Perlakuan Panas Yang Di Dinginkan DenganUdara,Air dan Oli Menggunakan Metode Vickers - Rizky Auditya Putra; Junaidi Junaidi; Fadly A Kurniawan (Jurnal Simetri Rekayasa, 2020)
ABSTRACT Steel is a material that we often use to make tools, both heavy and light equipment as well as food containers and many others. Steel is the material most widely used as an industrial material, because steel has various physical and mechanical properties. Carbon steel is an alloy between iron and carbon with small amounts of Si, Mn, P, S, and Cu. The nature of carbon steel is very dependent on the carbon content, if the carbon content increases, the strength and hardness will also increase. The property of steel which can undergo great deformation under the influence of high tensile stress without breaking or breaking is called the ductility property. The method used in this research is descriptive method, which is a method used to carefully test an object being studied so that accurate data will be obtained after data collection is complete, data processing will be carried out using a predetermined formula. Average value - diagonal average identification before heat treatment with a pressure load of 2000 grams at point 1 (top) 111.85 at point 2 (middle) 107.4 and at point 3 (bottom) 118.9. Number of hardness of the vickers with a load of 2000 grams at point 1 (top) 296.5 at point 2 (middle) 321.6 and at point 3 (bottom) 262.4. The average number of 1045 carbon steel testing before heat treatment is 293.5. From the conclusion of the study using 1045 carbon steel steel, there can be differences in the average diagonal identification value after heat treatment using water as a coolant with a pressure of 2000 grams at point 1 (above) 71 at point 2 (center) 131.80 and at point 3 ( bottom) 93. The number of vickers hardness with a load of 2000 grams at point 1 (top) 735.8 at point 2 (middle) 213.5 and at point 3 (bottom) 428.8 The average number of testing 1045 carbon steel after heat treatment with water as a coolant is 459.37. The diagonal mean value of identification after heat treatment using oil media as a coolant with a pressure load of 2000 grams at point 1 (above) 96.81 at point 2 (center) 107.54 and at point 3 (bottom) 100.09. Vickers hardness figure with a load of 2000 grams at point 1 (top) 395.7 at point 2 (center) 320.7 at point 3 (bottom) 370.2. The average number of testing 1045 carbon steel after heat treatment using oil media as a coolant with a value of 362.20. The diagonal mean value of identification after heat treatment using air as a coolant with a pressure load of 2000 grams at point 1 (top) 132.51 at point 2 (center) 140.38 and at point 3 (bottom) 125.49. Vickers hardness figure with a load of 2000 grams at point 1 (top) 211.2 at point 2 (center) 188.2 at point 3 (bottom) 235.5. The average number of testing 1045 carbon steel after heat treatment using air as a coolant with a value of 211.63. Keywords: steel, carbon steel, properties of carbon steel, hardness test, before and after heat treatment with water, oil, air as a coolant